Induced systemic resistance in beet plants infected with Meloidogyne javanica - Debia, Paula J. G.; Bolanho Barros, Beatriz C.; Puerari, Heriksen H.; Ferreira, Julio C. A. [UNESP]; Dias-Arieira, Claudia R. (Inst Investigaciones Agropecuarias, 2021)
Root-knot nematode infection has a direct and negative impact on the commercial value of beet (Beta vulgaris L.) tubers. The aim of this study was to evaluate induced resistance in beet tuberous roots infected with different population levels of Meloidogyne javanica (Treub, 1885) Chitwood, 1949. Plants were inoculated with increasing inoculum levels (0, 1500, 5000, and 10 000 eggs + juveniles [J2]) and treated with different products that can potentially induce resistance: mannan-oligosaccharides (MOS), citrus biomass, and acibenzolar-S-methyl (ASM). Vegetative, nematological, and enzymatic parameters were evaluated after 60 d. In general, when compared to the control (water), inducers did not promote a positive effect on tuber diameter and weight, regardless of the inoculum level. Only the weight of plants inoculated with 5000 eggs + J2 and treated with citrus biomass (40.70 g) increased compared with the control (32.38 g). The treatments did not reduce the number of galls, nematodes per root system, and nematodes per gram of root. Resistance inducers increased catalase activity (CAT) and phenylalanine ammonia-lyase (PAL) and MOS and ASM were the most effective. The highest CAT activity was for ASM and 5000 eggs + J2, resulting in 42.44% compared with the control. The MOS and ASM exhibited the highest PAL activity (0.22 and 0.15 mg trans-amino acid h(-1) mg(-1) protein, respectively) compared with the control (0.03 mg trans-amino acid h(-1) mg(-1) protein) in uninoculated plants. Results led us to conclude that inducers should not be used in isolation to control nematodes in beet. However, deformed tubers can be used in manufacturing, thus preventing food waste. In addition, new rates and application intervals should be evaluated to help control nematodes in beet plants.
Keywords: Beta vulgaris; induced resistance; root-knot nematodes; vegetative characteristics